Calculating tragedy : assessing the costs of terrorism - Bruno S. Frey; Simon Luechinger; Alois Stutzer (Center for Economic Studies and ifo Institute (CESifo), 2004)
The trends and consequences of terrorist activities are often captured by counting the number of incidents and casualties. More recently, the effects of terrorist acts on various aspects of the economy have been analyzed. These costs are surveyed and put in perspective. As economic consequences are only a part of the overall costs of terrorism, possible approaches for estimating the utility losses of the people affected are discussed. Results using the life satisfaction approach, in which individual utility is approximated by self-reported subjective well-being, suggest that people's utility losses may far exceed the purely economic consequences.
Keywords: I31; H56; D74; 330; terrorism; subjective well-being; life satisfaction; utility loss; Politische Gewalt; Soziale Kosten; Lebensqualität; Wohlfahrtseffekt; Theorie; Lebenszufriedenheit